Postdischarge Feeding of Very-low-birth-weight Infants: Adherence to Nutrition Guidelines. Issue 3 (September 2018) - Francis, Jane; Unger, Sharon; Bando, Nicole; Vance, Ashleigh; Gibbins, Sharyn; Kiss, Alex; Church, Paige; Sellen, Daniel; O'Connor, Deborah L.
ABSTRACT: Objectives: Infant feeding guidelines are important public health strategies to promote optimal growth, development, and chronic disease prevention, but their effectiveness is contingent upon families' ability to adhere to them. Little is known of adherence to guidelines among nutritionally vulnerable infants, specifically those born very-low-birth-weight (VLBW) (<1500 g). This study investigated whether postdischarge feeding practices for VLBW infants align with current recommendations and explored parental and infant baseline sociodemographics related to these practices. Methods: Prospectively collected data from families of 300 VLBW infants participating in a randomized clinical trial (ISRCTN35317141) were used. Baseline demographics were obtained at enrollment and postdischarge feeding practices via monthly telephone questionnaires to 6 months corrected age (CA). Results: At discharge, 4 and 6 months CA, 72%, 39%, and 29% of infants received any amount of mother's milk, respectively; exclusive breast-feeding rates were 49%, 20%, and 6%, respectively. Among infants receiving mother's milk, rates of vitamin D supplementation were ≥83%. Recommendations for introducing solids between 4 and 6 months CA were followed by 71% of the cohort and for iron supplementation by 58%. Overall, 12% of infants adhered to all aforementioned recommendations. Mothers with university degrees were more likely to provide mother's milk, whereas mothers of Middle Eastern/South Asian ethnicity were less likely to provide mother's milk. Conclusions: Low rates of partial and exclusive breast-feeding of VLBW infants to 6 months CA were reported. Overall adherence to iron supplementation was low. Strategies to provide increased support for mothers identified as at-risk should be developed. Abstract : Supplemental Digital Content is available in the text